Interleukin 6 and Interleukin 17a Enhance Proliferation and Differentiation of Murine Osteoblast and Human Foetal Osteoblast Cell Lines - S, Shaminea; TP, Kannan; MN, Norazmi; AA, Nurul (IIUM Medical Journal Malaysia, 2014)
Introduction: Cytokines have been gaining great focus due to their role in enhancing osseointegration as well as their potential in bone reconstruction. Osseointegration often faces complications in its compatibility with the implant due to rejection by the recipients own immune system. Therefore, extensive studies are being carried out to enhance osteoblast development to minimize such complication. The aim of this study was to determine the effect of different concentrations of Interleukin 6 (IL-6) and Interleukin 17a (IL-17A) in the proliferation and differentiation of murine and human osteoblasts. Methods: Various concentrations (5, 10, 25 and 50 ng/ml) of rIL-6 and rIL-17A were tested on both murine osteoblast (MC3T3-E1) and human feotal osteoblast (hFOB) cell lines using [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] (MTS) and alkaline phosphatise (ALP) assays. MTS was carried out at 24, 48, 72, 96 and 120 hours while ALP assay was done on day 1, 3, 7, 10 and 14. Results: MC3T3-E1 cells showed steadier proliferation and differentiation compared to hFOB. Both cell lines expressed responses in dose-dependent manner. The concentration of 10ng for IL-6 and IL-17A in the case of MC3T3-E1 cell line was found to be the most suitable for further studies. Conclusion: IL-6 and IL-17A enhance proliferation and ALP activity of both MC3T3-E1 and hFOB cell lines.